'I don’t have any emotions': feeling rules and surface acting in the emergency department … - Kirk, Katherine L. (2019)
The National Health Service (NHS) in England is under significant pressure. It is undeniable that the challenges facing the NHS have implications for the staff tasked with delivering care. Low rates of well-being have a direct impact on the quality of care delivered (Boorman, 2009). English nurses’ rates of stress, burnout and intention to leave the profession are among the highest in Europe and are higher than those in America (Aiken et al, 2012). Despite evidence showing the importance of positive nurse well-being, the emotional component of the role (a great influencer in well-being) (Warren, 2016; Johnson and Spector, 2007), is overlooked (Smith, 2012). An integral part of nursing is often neglected: the emotional labour of nursing. I have applied Hochschild’s theory of emotional labour to a previously unexplored clinical speciality: emergency care. Emergency departments (EDs) are struggling to meet demand, with increasing patient attendance over the last 70 years (The King’s Fund, 2018) and intense government targets (NHS England, 2018). In spite of these challenges, and the nature of EDs, an exploration of ED nurses’ emotional labour is missing from current understanding. We know little of how the ED environment influences the management of emotion. There is also limited knowledge of how nursing specialties, such as emergency care, drive the ‘speciality-specific’ feeling rules. The ED therefore offered a fitting case study to explore and contribute to the concept of emotional labour. Ethnography, through an interpretivist philosophy, enabled immersion in the ED setting, gathering the lived experiences and narratives of the ED nursing team. I undertook direct and first-hand observations, using an ethnographic approach. This allowed room for the dynamism of the setting, workload and pace. Semi-structured interviews were also undertaken with ED staff and the wider ‘well-being’ team. I used two departments for a rich and illuminative dataset. I firstly aimed to understand how the environmental, institutional and organisational dynamics of the ED instrumented the emotional labour. I found that elements of time and space were ‘moderators’ of ED nurses’ emotional labour – in essence, understanding these moderators’ integrated relevance offers the first contribution to knowledge. Understanding the moderators of emotional labour from an organisational ‘meso-level’ perspective, in addition to the study of the more familiar micro level exploration is of interest to those outside of the case study. In particular, those studying organisational behaviour and sociology. Secondly, I aimed to understand the feeling rules driving and underpinning this behaviour. I found that ED nurses’ feeling rules were grown from the distinctive context and that four feeling rules drove their emotional labour, offering a further contribution. These contributions are aimed at both practice based and academic nursing audiences. The recommendations from this thesis relate to working environments and nursing education. Although an ED case study was utilised, the findings can be applied to other healthcare settings, specialties and professionals, along with organisations outside of health. In addition, the findings are applicable to healthcare policy.